Raman spectroscopy a promising technique for investigations of metallothioneins. - Torreggiani, Armida; Tinti, Anna (Metallomics : integrated biometal science, 2010)
Metallobiomolecules are highly elaborated coordination complexes, and their fundamental metal-ligand interactions are critical components of metalloprotein folding, assembly, stability, electrochemistry, and catalytic function. Herein, we have described the benefits in using Raman spectroscopy to define the metal-ion binding properties of MTs toward metal ions such as Zn(ii) and Cd(ii). In particular, this vibrational technique can shed light on the secondary structures eventually present in MTs and the ligands involved in metal coordination. The oxidation state of Cys residues and their participation in the metal chelation can be clearly defined, as well as the eventual involvement of His residues. With regards to exogenous metal ligands such as sulfide anions, their presence can be identified by some marker bands whose intensity is linearly correlated with sulfide/metal molar ratio. Finally, Raman can be also an useful tool for providing information on the favourite sites of the radical attack and radical-induced modification in protein folding. In conclusion, many advantages such as the capability of defining local regions in large complexes and detecting several structural features at the same time, the ability in supporting mechanisms, as well as the requirement of low sample amount, make to propose Raman spectroscopy, in coupling with analytical techniques such as atomic emission spectroscopy, gas chromatography, and circular dichroism, as one of the most promising experimental strategies in the research on structure-activity relationships in MTs.
Keywords: copper; Copper: chemistry; Copper: metabolism; metallothionein; Metallothionein: chemistry; Metallothionein: metabolism; Spectrum Analysis, Raman; Spectrum Analysis, Raman: methods; Structure-Activity Relationship; Zinc; Zinc: chemistry; Zinc: metabolism

Adsorption of Zn(II) in aqueous solution by activated carbons prepared from evergreen oak (Quercus rotundifolia L.). - Gómez-Tamayo, M Del Mar; Macías-García, Antonio; Díaz Díez, M Angeles; Cuerda-Correa, Eduardo M (Journal of hazardous materials, 2008)
In the present work activated carbons have been prepared from evergreen oak wood. Different samples have been prepared varying the concentration of the activating agent (H(3)PO(4)) and the treatment temperature. The yield of the process decreases with increasing phosphoric acid concentrations. Furthermore, high concentrations of activating agent lead to mainly mesoporous activated carbons to the detriment of the microporous texture. Treatment temperatures up to 450 degrees C lead to a progressive increase of the micro- and mesopore volumes. Values of specific surface area (S(BET)) as high as 1723 m(2) g(-1)have been obtained using appropriate phosphoric acid concentrations and treatment temperatures. The samples prepared have been successfully used in the removal of Zn(II) from aqueous solutions. From the adsorption kinetic data it may be stated that the equilibrium time is, in all cases, below 170 h. The adsorption process as a rule becomes faster as the mesopore volume and specific surface area of the samples increase. The adsorption isotherms in liquid phase point out that the adsorption capacity (n(0)(s)) and the affinity towards the solute (K(ci)) are higher for the sample showing the most developed mesoporous texture and surface area as well.
Keywords: Adsorption; Carbon; Carbon: chemistry; Hydrogen-Ion Concentration; Quercus; Solutions; Water Pollutants, Chemical; Water Pollutants, Chemical: chemistry; Water Purification; Water Purification: methods; Wood; Zinc; Zinc: chemistry

Leaf accumulation of trace elements and polycyclic aromatic hydrocarbons (PAHs) in Quercus ilex L. - De Nicola, F; Maisto, G; Prati, M V; Alfani, a (Environmental pollution (Barking, Essex : 1987), 2008)
Quercus ilex L. leaves were collected four times in one year at six urban sites and one remote area in order to determine trace element and PAH accumulation through concomitant analyses of unwashed and water-washed leaves. Both unwashed and washed leaves showed the highest amounts of trace elements and PAHs in the urban area. Unwashed leaves showed greater differences between urban and remote areas and among the urban sites than washed leaves for trace element and PAH concentrations. Water-washing resulted in a significant (P<0.001) decrease in leaf concentrations of Cr, Cu, Fe, Pb, V and Zn. By contrast, Cd and total PAH concentrations showed no differences between unwashed and washed leaves.
Keywords: Air Pollutants; Air Pollutants: analysis; Aromatic; Aromatic: analysis; Atomic; biomonitoring; cadmium; Cadmium: analysis; chromium; Chromium: analysis; Cities; copper; Copper: analysis; Environmental Monitoring; Environmental Monitoring: methods; Iron; Iron: analysis; Italy; lead; Lead: analysis; PAHs; Plant Leaves; Plant Leaves: chemistry; Polycyclic Hydrocarbons; Quercus; Quercus ilex L.; Spectrophotometry; Trace Elements; Trace Elements: analysis; Unwashed and washed leaves; Vanadium; Vanadium: analysis; Zinc; Zinc: analysis

Leaf accumulation of trace elements and polycyclic aromatic hydrocarbons (PAHs) in Quercus ilex L. - De Nicola, F.; Maisto, G.; Prati, M. V.; Alfani, A. (Environmental pollution (Barking, Essex : 1987), 2008)
Quercus ilex L. leaves were collected four times in one year at six urban sites and one remote area in order to determine trace element and PAH accumulation through concomitant analyses of unwashed and water-washed leaves. Both unwashed and washed leaves showed the highest amounts of trace elements and PAHs in the urban area. Unwashed leaves showed greater differences between urban and remote areas and among the urban sites than washed leaves for trace element and PAH concentrations. Water-washing resulted in a significant (P<0.001) decrease in leaf concentrations of Cr, Cu, Fe, Pb, V and Zn. By contrast, Cd and total PAH concentrations showed no differences between unwashed and washed leaves.
The following values have no corresponding Zotero field: accession-num: 17892907
Keywords: Air Pollutants; Air Pollutants: analysis; Aromatic; Aromatic: analysis; Atomic; biomonitoring; cadmium; Cadmium: analysis; chromium; Chromium: analysis; Cities; copper; Copper: analysis; Environmental Monitoring; Environmental Monitoring: methods; Iron; Iron: analysis; Italy; lead; Lead: analysis; PAHs; Plant Leaves; Plant Leaves: chemistry; Polycyclic Hydrocarbons; Quercus; Quercus ilex L.; Spectrophotometry; Trace Elements; Trace Elements: analysis; Unwashed and washed leaves; Vanadium; Vanadium: analysis; Zinc; Zinc: analysis